The changes in Japanese university education amid Сovid-19 pandemic: the implementation of distance learning - Baiseitova, D. (Journal of Oriental Studies, 2023)
The COVID-19 pandemic made distance learning necessary for a much wider audience than before. As a result, educational institutions have been forced to develop or accelerate online learning in order to provide teachers and students with the most up-to-date technology as quickly as possible. Japan is a world leader in high-tech, but lag behind in the implementation and use of technology in university systems. Although the COVID-19 pandemic crisis has brought challenges and worries that teachers, students and their parents have never faced before, the current situation may offer Japanese universities a chance to advance in terms of ICT use, increase their e-learning readiness by improving infrastructure, capacity building of faculty and students, etc. The development of communication technology has a profound impact on the traditional system of Japanese education, With the worldwide emphasis on distance learning, it can be assumed that challenging times in Japanese education may also bring excellent opportunities, and this important educational model will continue to improve, becoming more effective and less complicated. The rapid shift to online teaching and the need to combine it with face-to-face teaching soon led to the search for a variety of practices, and with them, a variety of terminology. In Japanese universities, the combination of online and face-to-face teaching will expected to be the way forward for university education in the "post-coronary" era. In anticipation of this, it is worthwhile to put these terms in perspective and consider their characteristics, challenges and possibilities. The aim of this paper is to overview the changing nature of ’distance learning’ in Japanese universities, as well as to describe ’hybrid’ education, which combines face-to-face and online teaching. The study is descriptive in order to determine the specifics of the changing nature of ’distance learning’ in Japanese universities. This article summarises the events that have occurred in university education as a result of the new coronavirus, citing documents from the Ministry of Education, Culture, Sports, Science and Technology (MEXT) and media reports. Next, it summarises ’hybrid’ learning, which combines face-to-face and online teaching.